Manajemen Laba Aktivitas Rill Dalam Bingkaian Teori Akuntansi Positif - Kurniawansyah, Deddy; Mahendrawati, Dian (E-Jurnal Akuntansi; Vol 33 No 10 (2023), 2023)
Positive accounting theory is the basis for describing the reasons managers take opportunistic actions regarding the accounting policies used. Managers' opportunistic behavior towards profit regulation causes the quality of financial reports to decline. This research aims to examine the influence of political connections and bonus compensation on real activity earnings management. Manufacturing companies listed on the Indonesian Stock Exchange from 2016 to 2022 represent the population of this study. The sampling technique for this research uses the census method. The data analysis technique uses path analysis assisted by SmartPLS 3.0. The research results show that bonus compensation and political connections influence real activity earnings management. This research provides theoretical contributions to strengthen the three hypotheses of positive accounting theory. This research provides a practical contribution for investors as a strategy in determining investment in companies that produce quality financial reporting with minimal risk of conflict of interest. The contribution for the government is to strengthen the tax law revision policy to reduce earnings management practices. Keywords: Politic; Bonus; Earning Management; Real Activities